Professional Competence in School Leadership: Reflections on Implementation in Penggerak School - Zuhro, Nurul Shofiatin (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2024)
The principal is a teacher with the responsibility of leading and managing a school to improve the quality of education. In the implementation of the Merdeka Curriculum, principals must possess professional competencies in leadership, as this will influence decision-making in school leadership, thereby facilitating a student-centered learning transformation. This study aims to explore self-reflections on the professional competencies of school principals in school leadership at the School Movement Program in Surakarta City and Klaten Regency. The professional competency model for school principals is an essential element in the implementation of the Merdeka Curriculum, as outlined in the Perdirjen Regulation No. 7327 of 2023 on the Model of School Principal Competencies. The research design used is a qualitative research model to describe the achievement of professional competencies of school principals in leading schools. The sample was determined using purposive sampling, namely school principals in schools participating in the School Movement Program, consisting of three schools in Surakarta City and seven schools in Klaten Regency. The data analysis technique used in this study employs thematic analysis, which identifies themes or patterns in the data obtained through interviews and reflective journals. The results of this study indicate that in the implementation of professional competencies, school principals are able to achieve expert, competent level.